Mitigasi Risiko Volatilitas Harga Bawang Merah di Jawa Timur - Irzaq Galuh Pranata; Dwi Putri Sunaryanti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Fluctuations in shallot prices have a significant impact on farmers and other stakeholders. In this context, farmers are often the biggest losers due to price instability, as they have no control over the timing of their product sales, which means they cannot take advantage of more favorable prices during price spikes. On the other hand, price fluctuations affect not only farmers' income but also their farming decisions. Understanding this phenomenon is crucial for policymakers and stakeholders in the agricultural sector to mitigate risks and improve food security, especially for shallot farmers. This study aims to analyze how much price fluctuations and price disparities of shallots occur in East Java and which areas should be the primary concern due to such high fluctuations. To investigate this, disparity analysis using convergence models and price fluctuation analysis using the coefficient of variation (CV) approach were used. This study found that shallot price fluctuations in East Java are highest in the Nganjuk Regency. Interestingly, Nganjuk Regency is the center of shallot production in East Java. In addition, it was also found that areas bordering Nganjuk Regency, such as Madiun Regency, Bojonegoro Regency, Ponorogo Regency, and Pacitan Regency, experienced relatively high price fluctuations. The value of disparity based on the coefficient in the regression model of shallot price comparison in Indonesia shows a value of β < 1. This means that the level of shallot price fluctuations in East Java tends to be high, as evidenced by the CV value in most areas, which is classified as high.